Sistem informasi kemitraan bank sampah induk rumah harum - Malik Ardhiansyah; Cahyani Budihartanti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The waste bank is one of the containers for the process of collecting and sorting waste that can be recycled or reused. One of them is the Main Garbage Bank, Rumah Harum Depok, which has a partnership system that comes from organizations or individuals to collaborate in waste management. With the waste transaction system and partner registration that still relies on paper media as a tool to run the system, it often results in tucked documents and even disappears. These problems can be overcome by building a website-based partnership information system, to facilitate the partner registration process and more effective management of incoming and outgoing waste transaction data. The system development method used is the waterfall model using the CodeIgniter framework, MySQL database server and Apache web server, while the test is carried out using the Black Box Testing method. With this website-based information system, it can make it easier for the Rumah Harum Garbage Bank to manage waste transactions and make it easier for partners to register.